Heart beats rate indicators and structure of elite football referees' and their assistants' motor functioning in competition period - T. G. Chopilko; S.M. Berezka (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to analyze structure of motor functioning and heart beats rate indicators in elite football referees' and their assistants' competition activity. Material: in the research 15 referees and referees' assistants of Ukrainian Prime League, 30 referees and referees' assistants of first and second professional leagues of Ukraine participated. Observations over referees' movements in 21 professional matches of Ukrainian professional leagues were fulfilled. Distance, passed by a referee in one match was determined. Results: It was found that during one match referee (depending on his functions - referee or referee's assistant) passes distance from 6000 to 12 000 meters. This scope of motor functioning depends also on motor activity of players and qualification level of teams-participants in the match. Motor actions of referees' assistants change every 5 seconds during a match. During one match referee's assistants fulfill about 20 sprints and 74 accelerations. A high temp of match total distance makes 1.2 km. Conclusions: Referees' and referee assistants' motor functioning and heart beats rate indicators can vary from aerobic-restoration to anaerobic-glycolytic zone. This fact shall be considered when planning program on special physical training. It should be noted that with heart beats rate of more than 180 bpm concentration of attention significantly weakens as well as ability to take prompt and correct decisions. In such cases probability of mistakes significantly increases.